2019
DOI: 10.1111/jgs.15790
|View full text |Cite
|
Sign up to set email alerts
|

Differences in National Diabetes Treatment Patterns and Trends between Older and Younger Adults

Abstract: BACKGROUND/OBJECTIVES: The treatment of type 2 diabetes in older adults requires special considerations including avoidance of hypoglycemia, yet variation in diabetes treatment with aging is not well understood. In this study, we compared nationally representative diabetes treatment patterns and trends between older adults (≥65 y) and younger adults (30–64 y). DESIGN: Repeated cross-sectional physician surveys from 2006 to 2015. SETTING: The National Ambulatory Medical Care Survey, an annual probability sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Consistent with other studies, we found that insulin use substantially increased over time suggesting that there may be protective factors countering this such as more effective diabetes treatment and hypoglycemia prevention strategies; further study is needed to clarify this. [41][42][43] We found substantially different rates of hypoglycemia hospital utilization among patient subgroups with known clinical hypoglycemia risk factors. Notably, insulin users had approximately 10-fold higher rates than those using diabetes medications with a low risk for hypoglycemia, and approximately fivefold higher rates than users of insulin secretagogues.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Consistent with other studies, we found that insulin use substantially increased over time suggesting that there may be protective factors countering this such as more effective diabetes treatment and hypoglycemia prevention strategies; further study is needed to clarify this. [41][42][43] We found substantially different rates of hypoglycemia hospital utilization among patient subgroups with known clinical hypoglycemia risk factors. Notably, insulin users had approximately 10-fold higher rates than those using diabetes medications with a low risk for hypoglycemia, and approximately fivefold higher rates than users of insulin secretagogues.…”
Section: Discussionmentioning
confidence: 74%
“…Despite temporal changes in the landscape of diabetes treatment, we found that rates of hospital utilization for hypoglycemia decreased slightly from 2009 to 2014, and were stable from 2016 to 2019. [41][42][43] It is possible that temporal trends in hypoglycemia were driven by differences in the study population, however the stability of the demographic and clinical characteristics of the cohort makes this unlikely. Consistent with other studies, we found that insulin use substantially increased over time suggesting that there may be protective factors countering this such as more effective diabetes treatment and hypoglycemia prevention strategies; further study is needed to clarify this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However long-term treatment of patients with type 2 diabetes often still requires the introduction of exogenous insulin to provide the best control of plasma glucose levels, once the initial treatment paradigms have failed. Moreover, in recent years, in spite of the availability of new agents, optimal control glycemia has not improved [ 16 ]. Some have argued for a broader use of pioglitazone because of its potential to prevent the loss of pancreatic β cell function and in particular, its efficacy in reducing cardiovascular disease, which remains the major cause of morbidity and mortality in both diabetic and prediabetic patients [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Although use of sulfonylureas has been decreasing over the past decade, they remain the second most common oral diabetes medication class after metformin, used in nearly one third of ambulatory visits for patients with type 2 diabetes in the United States. 15,16 Sulfonylureas have drug-drug interactions with a number of antimicrobials causing a substantially higher risk of hypoglycemia when used together. [17][18][19][20][21] The fluoroquinolones ciprofloxacin, levofloxacin, and moxifloxacin have been associated with both hyperglycemia and hypoglycemia by altering pancreatic β-cell signaling.…”
mentioning
confidence: 99%